Extracurricular Band Activities at Sma Negeri 1 Seluma, Bengkulu Province - Harisnal; Parta Wijaya, Thomas (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This study aims to describe "extracurricular band activities at SMA Negeri 1 Seluma, Bengkulu Province." This type of research is qualitative and conducted using descriptive methods. Data collection techniques include observation, interviews, literature studies, and documentation. Data analysis techniques by means of data collection, data reduction, data presentation, and conclusion drawing The results of research on "Band Extracurricular Activities at SMA Negeri 1 Seluma Bengkulu Province" The design of extracurricular band activities is to design training activities for two times a week and the formation of a management structure so that activities run smoothly and are directed. The musical instrument equipment used is an electric guitar, bass, drums, keyboards, microphones for vocals, and amps. The activities carried out by students are individual practice, group practice, group formation, and playing songs. Teachers always monitor the development of students who take part in extracurricular band activities, and students are always under the supervision of coaches and trainers during extracurricular band activities. The band's extracurricular achievements are being able to play songs and master techniques, being able to perform at school events, and participating in student-level band festival events.